1976
DOI: 10.1016/0072-968x(76)90016-4
|View full text |Cite
|
Sign up to set email alerts
|

Palmaris longus, anteductor of the thumb An experimental study

Abstract: Palmaris longus contributes to the anteposition and pronation of the thumb under circumstances. It is however restricted by its medial tendon which runs into the palmar aponeurosis. The diversion of this tendon and the mobilisation of the muscular head of the abductor pollicis brevis arising from its lateral tendon will substantially accentuate the rôle of palmaris longus as a muscle of the thumb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…It has been suggested (Standring, 2007), that the main function of the PLM is not wrist flexion, but rather resisting horizontal shearing forces in a distal direction, as in using a golf club. Another under-reported function is abduction of the thumb (Tubiana, 1973;Fahrer and Tubiana, 1976). This action has been attributed to a lateral slip of the tendon of the PLM that normally inserts onto the abductor pollicis brevis (Reimann et al, 1944;Oudit et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…It has been suggested (Standring, 2007), that the main function of the PLM is not wrist flexion, but rather resisting horizontal shearing forces in a distal direction, as in using a golf club. Another under-reported function is abduction of the thumb (Tubiana, 1973;Fahrer and Tubiana, 1976). This action has been attributed to a lateral slip of the tendon of the PLM that normally inserts onto the abductor pollicis brevis (Reimann et al, 1944;Oudit et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Traction to the palmar aponeurosis was reported to aid the abduction of the thumb (Fahrer, 1973). Fahrer and Tubiana (1976) suggested that in cases of paralysis of abductor pollicis brevis, the tendon of PLM could be freed from the flexor retinaculum, to increase the function of thumb abduction (Tubiana, 1973).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…9,10 PL acts as a we ak fle xor of the wrist, plays a ro le in sta bi li za ti on of the pal mar fas ci a and contri bu tes to an te po si ti on and pro na ti on of the thumb. 11 The aim of this study was to eli cit the pre valen ce of PL age ne sis in the Afg han po pu la ti on and to com pa re the re sults with the pre vi o usly re por ted li te ra tu re. The as so ci a ti on of pal ma ris lon gus age ne sis with the si de and sex was al so analy zed sta tisti cally.…”
mentioning
confidence: 99%